Bilateral thalamic internal medullary lamina involvement in a case of dengue encephalitis - Ahmad, S.B.; Cheong, C.S.; Lim, S.Y.; Rahmat, K.; Rozalli, F.I.; Sekaran, S.D.; Sulaiman, H.; Ponnampalavanar, S.; Lim, K.S.; Tan, C.T. (ASEAN Neurological Association, 2016)
There are 50-100 million dengue infections each year, but dengue encephalitis is relatively uncommon. The aetiology of neuronal injury is proposed to be due to direct viral neurotropism or host immune response-mediated inflammation causing neuronal damage. We report a case of severe dengue encephalitis, presenting during the acute viraemic phase of the disease. This was associated with inflammation and haemorrhage of the internal medullary lamina of both thalami which, to our knowledge, has not yet been reported in other infections of the central nervous system.